2010
DOI: 10.1158/1535-7163.mct-09-0800
|View full text |Cite
|
Sign up to set email alerts
|

IFN-β Restricts Tumor Growth and Sensitizes Alveolar Rhabdomyosarcoma to Ionizing Radiation

Abstract: Ionizing radiation is an important component of multimodal therapy for alveolar rhabdomyosarcoma (ARMS). We sought to evaluate the ability of IFN-β to enhance the activity of ionizing radiation.Rh-30 and Rh-41 ARMS cells were treated with IFN-β and ionizing radiation to assess synergistic effects in vitro and as orthotopic xenografts in CB17 severe combined immunodeficient mice. In addition to effects on tumor cell proliferation and xenograft growth, changes in the tumor microenvironment including interstitial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Orthotopic intramuscular (IM) ARMS xenografts were established in male CB-17 severe combined immunodeficient mice (Taconic, Hudson, NY), as previously described [23]. The size of the IM tumors was estimated by measuring the volume of the normal left calf and subtracting that from the volume of the tumor-bearing right calf.…”
Section: Methodsmentioning
confidence: 99%
“…Orthotopic intramuscular (IM) ARMS xenografts were established in male CB-17 severe combined immunodeficient mice (Taconic, Hudson, NY), as previously described [23]. The size of the IM tumors was estimated by measuring the volume of the normal left calf and subtracting that from the volume of the tumor-bearing right calf.…”
Section: Methodsmentioning
confidence: 99%
“…Because the newest class of anti-cancer agents, anti-angiogenic agents, alter tumor blood flow but may not substantially alter tumor size, CEUS is emerging as a promising modality for assessing response to these agents in adult cancers [20,21,34,35]. Our preclinical studies have shown that quantitation of US contrast agent flow into pediatric murine models of neuroblastoma and rhabdomyosarcoma allows accurate monitoring of changes in tumor blood flow induced by a variety of anti-angiogenic agents [2224]. …”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis in tumors was determined by terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling using a commercially available in situ apoptosis detection kit (Serologicals, Billerica, Massachusetts) as previously described 13 . Tumor cell proliferation was analyzed by staining formalin-fixed, paraffin-embedded sections (4 μm) with anti-Ki67 (rabbit monoclonal clone SP6; Neomarkers, Fremont, California).…”
Section: Methodsmentioning
confidence: 99%